An Act for the Abolition of the Slave Trade: The Effects of an Import Ban on Cape Colony Slaveholders - Igor Martins (African Economic History Network (AEHN), 2019)
Few could have foreseen the consequences when the British Parliament, in 1807, passed the Slave Trade Act that sought to abolish slave imports into the British Empire. From population decreases in the British Caribbean to increased prices in the Cape Colony, historical evidence suggests that the effects of the Act were felt far and wide even though commercialization of slaves was still possible within colonial territories. Using newly digitized historical datasets covering more than 40 years in two different districts of the British Cape Colony, this paper measures changes in slave ownership and acquisition patterns from a longitudinal perspective. This approach allows me to tease out the effects of the Act on farmers with different types of agricultural outputs, most notably crop and livestock farming, agricultural types with very different labor demands. The results show that livestock farmers, surprisingly, were more inelastic to the import ban in comparison to crop farmers. These results suggest that slaveholders could extract rents from the enslaved in a multitude of ways beyond agriculture production and calls for a broader theory of slavery as capital investment.
Keywords: N01; N27; N37; 330; Slavery; abolition; Cape Colony; economic history